The concept and features of information as a theoretical category - Banakh, Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
In article is considered the transformation of the interpretation of the term «information» as a theoretical category with the positions of the different scientific traditions, its features and content. The phenomenon of information is the basis of all information processes occurring in society, its nature and laws largely determine the practice of formation and appearance of the future information society. It is therefore important to determine the exact meaning of «information», which is one of the most controversial issues of modern jurisprudence. This is due, first of all, to the fact that the information and legal sphere is in a state of transition to a fundamentally new paradigm and is characterized by constant changes, so many theoretical problems, including categorical ones, remain underdeveloped. Particular attention is paid to the generalization and systematization of various approaches to the definition of the concept of «information». Today, scholars have conditionally identified three approaches to defining the concept of «information» as a theoretical category: cybernetic, philosophical and legal. The current Ukrainian legislation contains various definitions of the concept of «information», which is caused by the peculiarities of the need to regulate the relevant spheres of public life in view of the information and transformation processes in our country. The concept of «legal information» is analyzed and classified. The current tendency of interpretation of legal information is that legal information means the totality of information about the facts, processes and phenomena of modern society. There are different criteria for the classification of legal information. In particular, according to sources, legal information is divided into normative and non-normative. The priority is given to the unification of the concept of «information» in Ukrainian legislation.